THE INFLUENCE OF ALLOWANCES ON EMPLOYEE PERFORMANCE AT AGRICULTURAL OFFICE OF LUWU DISTRICT - Indriani Maulida Tajuddin; Abdi Akbar; Agung Widhi Kurniawan; Zainal Ruma; Tenri Sayu Puspitaningsih Dipoatmodjo (CURRENT ADVANCED RESEARCH ON SHARIA FINANCE AND ECONOMIC WORLDWIDE, 2023)
An allowance refers to additional payments, benefits, or privileges provided to employees by their employers, usually in addition to their regular salary or wages. These allowances are intended to support or compensate employees for certain expenses, hardships, or circumstances relating to their work or personal lives. This study aims to determine the effect of allowances on employee performance at the Luwu District Agriculture Service Office. The type of data used in this study is quantitative data obtained from questionnaires distributed to 52 individuals related to the problem being examined. The data were analyzed using a simple linear regression analysis method with the help of SPSS data processing to prove the hypothesis. The results of the study show that the allowance variable has a positive and significant effect on employee performance. Specifically, the study found that the higher the benefits obtained by an employee, the higher their performance level will be.